Using authentic material through an online platform to improve speaking skills performance in a group of children (2024)
ABSTRACT: This action research project explored whether the use of authentic materials through an online platform could help improve English speaking skills among students at Level 4 of the Programa de Inglés para Niños y Jóvenes at the University of Antioquia. The data collection instruments included a research journal, two diagnostic exams (administered at the beginning and end of the project), a focus group with the students, and an interview with the cooperating teacher. The data analysis indicated that the use of authentic materials in the activities assigned to students was beneficial in enhancing certain aspects of their speaking skills; however, the expected outcomes were not fully achieved. Furthermore, the online platform and regular practice were effective in boosting students’ motivation and increasing their self-confidence in speaking English. Although slight improvements were observed among students, it is recommended that a future implementation emphasizes the importance of students’ commitment, making participation mandatory, as inconsistent engagement may have impacted on the results.